Iron Is Filtered by the Kidney and Is Reabsorbed by the Proximal Tubule - Wareing, Mark; Smith, Craig P. (Frontiers in Physiology, 2021)
The aim of this study was to determine the iron (Fe) concentration profile within the lumen of the S2 renal proximal convoluted tubule (PCT) and to resolve whether this nephron segment transported iron. To do this we performed in vivo renal micropuncture on Wistar rats, collected PCT tubular fluid from superficial nephrons and measure iron concentration. Iron was present in pro urine and the Fe concentration profile along the S2 PCT suggested significant iron reabsorption. Proximal tubules were also microperfused in vivo with physiological solutions containing Fe, and Zn, Cu, Mn or Cd. Proximal convoluted tubules perfused with 12mol.l-1 55FeCl3 reabsorbed 105.2 ±12.7 fmol.mm-1.min-1 Fe, 435±52 pmol.mm-1.min-1 Na and 2.7±0.2 nl.mm-1.min-1 water (mean +/- SEM; n=19). Addition of ascorbate (1mmol.l-1) to the perfusate did not significantly alter Fe, Na or water reabsorption. Supplementing the control perfusate with 60mol.l-1 FeSO4 significantly decreased 55Fe uptake. Recalculating for the altered molar activity following addition of unlabeled Fe revealed a three-fold increase in Fe flux. Addition to the perfusate 12mol.l-1 CuSO4, MnSO4, CdSO4 or ZnSO4 did not affect Fe, Na or water flux. In conclusion; 1) In vivo, S2 PCTs of rat reabsorb a metabolically significant quantity of Fe; 2) Fe is reabsorbed along the PCT via a pathway that is insensitive to Cu, Mn, Cd or Zn. Together these data demonstrate for the first time the hitherto speculated process of renal iron filtration and subsequent tubular iron reabsorption in a living mammal.